2018
DOI: 10.1002/suco.201800036
|View full text |Cite
|
Sign up to set email alerts
|

Strength and microstructural analysis of concrete incorporating ash from sunflower seed shells combustion

Abstract: The aim of the study involves determining the added value of shells of sunflower seeds ash (SSA) as a mineral admixture in concrete and the effects/mechanisms through which it affects the concrete microstructure. The chemical effect of this type of ash was estimated by examining its chemical composition, pozzolanic activity index, and SEM investigation while its physical effect was observed at the level of concrete with ash incorporated. Four concrete mixtures with different shares of cement replacement by ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The hardened specimen was cured in a water bath and three cubes were tested for the 7th day test and the average value was taken. The pattern was followed for 14th day and 28th day tests also 19,20 . The graph represented below as Figure 2 shows the results obtained for the compression test.…”
Section: Methodsmentioning
confidence: 90%
“…The hardened specimen was cured in a water bath and three cubes were tested for the 7th day test and the average value was taken. The pattern was followed for 14th day and 28th day tests also 19,20 . The graph represented below as Figure 2 shows the results obtained for the compression test.…”
Section: Methodsmentioning
confidence: 90%
“…Finally, the filler fills the small pores between the fine powder particles and the cement particles according to the particle size distribution of the cement and the filler. All these effects influence the properties of the cement paste and thus the properties of the concrete/mortar . Many reports investigating the use of waste and by‐product materials as pozzolan in cement replacement exist in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…All these effects influence the properties of the cement paste and thus the properties of the concrete/mortar. [14][15][16] Many reports investigating the use of waste and by-product materials as pozzolan in cement replacement exist in the literature. [17][18][19][20] It has been found that the use of the pozzolan as complementary cementitious materials provides a noticeable increase in the mechanical and properties of the mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the recycling of these crusts through the usage in concrete as cement materials aids significantly in producing an environmentally friendly concrete and decreases cement usage. Nevertheless, previous attempts have been made to reuse both walnut shells as coarse or fine aggregate 47 – 50 and sunflower ash in micro size 51 , 52 within concrete. However, no previous research used walnut shells ash and sunflower ash at nano size.…”
Section: Research Significancementioning
confidence: 99%